PENGARUH ANIMOSITY PRODUCT JUDGEMENT DAN BOYCOTT PARTICIPATION TERHADAP PURCHASE UNWILLINGNESS PRODUK PRO-ISRAEL - Ulfatunnisa Ulfatunnisa; Dita Puruwita; Nadya Fadillah Fidhyallah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the influence of animosity, product judgment, and boycott participation on purchase unwillingness toward pro-Israel products among Generation Z in DKI Jakarta. The research employed a quantitative method with a survey approach. The population consisted of Generation Z individuals residing in DKI Jakarta who had previously consumed Starbucks products. A purposive sampling technique was used to select 150 respondents. Data were collected through questionnaires using a Likert scale. The data analysis was conducted using Structural Equation Modeling (SEM) with SPSS and AMOS software. The results indicate that animosity has a positive and significant effect on both boycott participation and purchase unwillingness but does not affect product judgment. Furthermore, boycott participation significantly influences purchase unwillingness, whereas product judgment does not. Additionally, boycott participation is proven to mediate the effect of animosity on purchase unwillingness, while product judgment does not serve as a mediator. This study contributes to marketing strategies that incorporate social values.